Inoculation of the fungi-static C. iranensis ZJW-6 accelerates compost maturation, enhances fertilizer efficiency, and increases the abundance of target microbes in spring and autumn compost - Wang, Dongchao; He, Jingqi; Li, Liangdong; Wu, Gaoyuan; Jiang, Zixian; Cang, Baifeng; Wu, Meikang; Nuo, Min; Liu, Zichen; Li, Jiaxuan; Xu, Shengbo; Ma, Xintong; et al. (Frontiers in Microbiology, 2025)
IntroductionStraw composting is an effective way of straw resource utilization, and inoculation of microorganisms can accelerate straw decomposition. This study initially investigated the effects of adding fungi-static C. iranensis (ZJW-6) on lignocellulose, humic acid, and bacterial communities during the spring and autumn composting of rice straw in Northeast China.MethodsZJW-6 is a cellulose degrading bacterium, which is used as the microorganism for composting inoculation. Four treatments are set up:spring composting with no bacteria added; spring composting with added bacteria, autumn composting without added bacteria, and autumn composting with added bacteria. The effects of adding microorganisms in spring and autumn composting on its physical and chemical properties and microbial community changes are explored.ResultsThe results demonstrated that ZWJ-6 altered the bacterial community composition by increasing the relative abundance of lignocellulose-decomposing bacteria and the Actinobacteriota phylum in both spring and autumn composting. This enhancement strengthened the functional contributions of the bacterial community during composting. Specifically, the degradation efficiencies of lignin, cellulose, and hemicellulose in straw composting increased by 7.63%–14.71%, 22.45%–97.76%, and 28.48%–41.71%, respectively. Additionally, the content of humic acid and nitrogen increased by 12.44%–38.27% and 4.56%–5.81%, respectively. Autumn composting showed better decomposition and maturity.DiscussionThe addition of ZJW-6 promotes the maturation of both spring and autumn compost decomposition, offering a new agricultural solid waste disposal options for the straw-returning cultivation model in the region. Overall, adding ZJW-6 to autumn straw compost is more suitable for rice-growing areas in northeastern China.